Nutrients cause grassland biomass to outpace herbivory - E. T. Borer (Nature Portfolio, 2020)
It is unclear whether terrestrial herbivores are able to consume the extra plant biomass produced under nutrient enrichment. Here the authors test this in grasslands using a globally distributed network of coordinated field experiments, finding that wild herbivore control on grassland production declines under eutrophication.